When unionisation is profitable for firms in network industries - Luciano Fanti; Domenico Buccella (Kiel Institute for the World Economy (IfW), 2017)
In an industry characterised by the presence of network effects, this paper investigates a duopolistic game in which firms may choose whether to bargain over wages and employment with unions or to face a competitive labour market (i.e. without unions). If unions are sufficiently risk-averse, it is shown that the presence of strong network effects makes unionisation the Pareto-efficient sub-game perfect Nash equilibrium outcome for firms. The issue of entry is also investigated.
Keywords: J51; L13; L20; 330; unionised oligopoly; competitive labour market; efficient bargaining; market entry and entry deterrence